The Significance of the Caste System of Balinese in the Modern Era: A Discourse of Cultural Communication - Sihombing, Lambok Hermanto (Komunitas, 2022)
Bali is an island and a province with a beautiful culture. Most Balinese are Hinduism. Like in any other country, Balinese Hinduism also adopts the caste system. The caste system in Hinduism means that people are classified based on their social status. Balinese people live in a complex caste system relationship that has continued to exist since the days of the kingdom in Indonesia. This research aims to know the perception of the Balinese local people against the caste system in the modern era. The method used in this research is by interviewing one local Balinese person from each caste who might be related and an expert from each caste, analyzed uy using the perspective of Arjun Appadurai. This research finds that the caste system is no longer a determinant of success in the modern era. However, the caste system still affects the way of communication among the people of Bali, and the imprints can still be found in the daily life of the locals.